2011
DOI: 10.3109/19390211.2010.542233
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Natural Product Formulations on Murine Dendritic Cells

Abstract: The popularity and availability of herbal extracts has increased dramatically over the last decade, providing an inexpensive manner of self-medication. Although the efficacy of individual extracts is currently being intensively studied, research regarding complex mixtures is limited. Therefore, we evaluated the effects of three complex formulations including BRC-301, a polyherbal extract; BRC-304, a mixture of vitamins, minerals, antioxidant enzymes, botanical extracts and carotenoids; and BRC-306, a proprieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…The effect of Plantago asiatica L. (ES-PL) seeds, a traditional Chinese medicine, was found to increase levels of MHC class II molecules and major co-stimulatory molecules on DCs, suggesting it may enhance antigen presenting abilities to primed T lymphocytes indicating functional maturation of DCs [ 24 ]. BRC-301 (a polyherbal extract), BRC-304 (a mixture of vitamins, minerals, antioxidant enzymes, botanical extracts, and carotenoids), and BRC-306 [a trademarked blend of Uncaria tomentosa (cat’s claw) and Phytolens] were found to affect the innate responsiveness of murine DCs and enhance their ability to stimulate T-cell-mediated immunity [ 25 ].…”
Section: Modulation Of DC Activitiesmentioning
confidence: 99%
“…The effect of Plantago asiatica L. (ES-PL) seeds, a traditional Chinese medicine, was found to increase levels of MHC class II molecules and major co-stimulatory molecules on DCs, suggesting it may enhance antigen presenting abilities to primed T lymphocytes indicating functional maturation of DCs [ 24 ]. BRC-301 (a polyherbal extract), BRC-304 (a mixture of vitamins, minerals, antioxidant enzymes, botanical extracts, and carotenoids), and BRC-306 [a trademarked blend of Uncaria tomentosa (cat’s claw) and Phytolens] were found to affect the innate responsiveness of murine DCs and enhance their ability to stimulate T-cell-mediated immunity [ 25 ].…”
Section: Modulation Of DC Activitiesmentioning
confidence: 99%
“…is an herbal medicine that can radiate the heat of the body for reducing heat. Recently it has been reported that the isoflavone component of soybean plants alleviates inflammatory symptoms of the skin caused by heat 16,17) . In particular, 7, 3', 4'-Trihydroxyisoflavone, a major metabolite of daidzein and genistein, has been reported to maintain the homeostasis of the skin barrier by increasing the expression of filaggrin in NC/Nga mice induced atopic dermatitis 13) .…”
Section: Introductionmentioning
confidence: 99%
“…BRC-301, a polyherbal extract, could modulate LPSinduced production of NO, TNF-α, and IL-6 in DC2.4 cells and BM-DCs, and enhanced the uptake of FITC-conjugated ovalbumin by BM-DCs (Miller et al, 2011). IBS-20, a 20-herb Chinese medicinal formula, or the component herb Coptis chinensis Franch.…”
Section: Extracts Of Immunosuppressive Chinese Herb or Herbal Mixturementioning
confidence: 99%